2019
DOI: 10.1128/aem.00177-19
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Limitation Impairs Pathogen Expansion and Biofilm Formation Capacity

Abstract: Multidrug-resistant bacterial pathogens are becoming increasingly prevalent, and novel strategies to treat bacterial infections caused by these organisms are desperately needed. Bacterial central metabolism is crucial for catabolic processes and provides precursors for anabolic pathways, such as the biosynthesis of essential biomolecules like amino acids or vitamins. However, most essential pathways are not regarded as good targets for antibiotic therapy since their products might be acquired from the environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…S1D ), suggesting that the amount of readily available methionine in the lung is very limited, not sufficient to rescue its auxotrophy. Indeed, the level of methionine in human serum was calculated to be as low as ∼20 μM ( 29 , 30 ), which was described as insufficient to support the growth of various auxotrophic bacterial pathogens ( 31 ), and we have also observed that this is not enough to rescue growth of the A. fumigatus ΔmetG ΔcysD auxotroph ( Fig. S1C ).…”
Section: Resultsmentioning
confidence: 91%
“…S1D ), suggesting that the amount of readily available methionine in the lung is very limited, not sufficient to rescue its auxotrophy. Indeed, the level of methionine in human serum was calculated to be as low as ∼20 μM ( 29 , 30 ), which was described as insufficient to support the growth of various auxotrophic bacterial pathogens ( 31 ), and we have also observed that this is not enough to rescue growth of the A. fumigatus ΔmetG ΔcysD auxotroph ( Fig. S1C ).…”
Section: Resultsmentioning
confidence: 91%
“…The increased expression of the methionine pathway by L. monocytogenes CTC1034 under HPP stress could explain, at least partially, the piezo-stimulation effect (which was enhanced by the presence of lactate) in the growth rate of L. monocytogenes CTC1034 cells surviving a HPP at 600 MPa for 3 min observed by Bover-Cid et al [ 11 ]. Since methionine is a key amino acid involved in enabling cell proliferation as precursor of anabolic pathways [ 72 ], the upregulation of the methionine biosynthesis due to lactate and HPP stresses could help L. monocytogenes cells to repair cellular membrane and enhance their subsequent proliferation. Nevertheless, further studies should be conducted to complement and support this.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria can increase their fitness in the host niche by producing metabolites, such as essential amino acids, to promote colonization [19], virulence [18,41], biofilm expansion [42], and rapid growth [40]. Methionine it is one of the scarce amino acid in physiological fluids but its importance cannot be underestimated.…”
Section: Discussionmentioning
confidence: 99%